THE ROLE OF CULTURE DIVERSITY IN INTERNATIONAL PROJECT TEAMS - Amirkhan B. Salimetov (Modern American Journals, 2025)
Today, international project teams are a key aspect of organizational strategy in multinational corporations as well as cross-border collaborations. Cultural diversity within these teams presents both opportunities and challenges for project execution, leadership, communication, and decision-making. This study investigates the role of cultural diversity through a comprehensive review of contemporary academic literature focusing on team performance, innovation, conflict resolution, and organizational outcomes. Drawing on frameworks such as cultural intelligence (CQ) and revised models of Hofstede's cultural dimensions, it highlights strategies for improving multicultural collaboration. Recommendations for project managers and organizations emphasize intercultural competencies, adaptive communication, and inclusive team cultures to enhance project success in a dynamic global business environment.